Shunt Compensation and Optimization of Nigerian 330Kv 34 Bus Power System using Metaphorless Rao-Type Algorithms (Nigerian Journal of Technology, 2022)
Power system networks suffer from power losses and bus voltage violations due to heavy loading at the various buses. As a consequence, there is a need for some sort of compensation at the heavily loaded bus points. In this paper, a novel type of optimizer with fast convergence and simplicity called Rao-1, which is based on metaphorless programming, is presented for the task of optimization with shunt compensation on Nigerian 330-kV power network. The application of this algorithm for optimal shunt compensation of the Nigerian 330kV, 34-bus power transmission network is presented. The results obtained by Rao-1 technique are compared with particle swarm optimization (PSO). The findings show that using shunt compensation generally improves the precision of objective function values even though at some trials there might be deviations. Comparative results also show the competitiveness and efficacy of proposed Rao-1 type algorithm in terms of fitness scores and computational run time.